Exploring Agriculturalists' Use of Social Media for Agricultural Marketing - Danielle White; Courtney Meyers; David Doerfert; Erica Irlbeck (Journal of Applied Communications, 2014)
The Internet has had a significant impact in how agriculturists get their information and how they communicate with consumers. The use of user-generated media, especially social media, now provides agriculturalists free and practically instantaneous channels through which to engage with their audience members. The purpose of this study was to explore agriculturalists’ use of social media for agri-marketing. This study used a qualitative research approach consisting of in-depth interviews with four agriculturalists who met certain criteria: an individual (1) working in agriculture, (2) using several social media platforms, and (3) using social media to market his/her own agricultural operation. Analysis of the interview transcripts identif ied seven emergent themes to address the three research objectives. Findings indicated participants became active using social media to combat dominant negative messages about production agriculture. Participants also discussed how they manage their social media presence and balance responsibilities. Overall, they were positive about the use of social media for their own operations and for the broader agricultural community. Additional analysis indicated some gender differences in regard to social media use. Recommendations for both practitioners and researchers are provided to further explore social media use in agriculture.